Contribution of Philosophy in globalized societies for a interdisciplinary training formación interdisciplinar - Mayos, Goncal (2023)
In the first part of the article, we will diagnose the situation, possibilities, difficulties and challenges of education in the face of the effects of turboglobalization and the COVID-19 pandemic. And in the second part we will show some contributions that, in our opinion, philosophy can carry out, as an interdisciplinary, intercultural discipline open to thinking about the present.